MODEL PEMBELAJARAN PEER GROUP UNTUK PENINGKATAN KEMANDIRIAN BELAJAR MAHASISWA - Anan Sutisna (Perspektif Ilmu Pendidikan, 2011)
The purpose of this research is to unveil the instructional model which can strengthen the self-learning competence of the university students. A peer group instructional model is choosen as the alternative model to develop. The research findings indicate that (1) the university studentsâ€™ learning tends to be textbook centered based instruction and does not motivate the students to develop their learning strategy, (2) peer group instructional model can improve the studentsâ€™ competence in self-learning, formulating the objectives, planning the strategy, utilizing learning resources, using media, comprehending the main ideas in the learning materials, exposing ideas, understanding learning networks, and measuring learning achievement.